Program PKB AISBER Dalam Membentuk Kompetensi Bahasa Dan Keagamaan Siswa - Siti Herlina; Gatot Sujono; Afif Zamroni (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2021)
This article aims to explain and analyze the implementation of the AISBER PKB program at SDN Mulyoagung Kec. Balen Kab. Bojonegoro. The type of research used is a case study which is a descriptive analysis. As for the approach using qualitative which is a research method that aims to understand the phenomena that occur in the research subject. Data collection techniques through interviews, observation, documentation. Data analysis techniques include: data collection (data collection), data condensation (data condensation), data presentation (data display), drawing conclusions (condution drawing). The results of the AISBER PKB program research are planned through a meeting with the school development team and then socialized which is attended by all parents / guardians of students, the teacher council, for its implementation through self-development, counseling services, and taught by class teachers, with the habituation of akhlakul karimah which is 15 minutes before carrying out learning in the classroom. After carrying out regular learning, students are given additional lessons for 30 minutes. The AISBER PKB program can minimize the negative impact of using gadgets with reciting and studying activities at home, able to increase the ability to learn Islam and languages ??including Arabic and English, make children have more religious knowledge and become more religious and have skills in foreign languages, especially Arabic and English.